(untitled) (Education in the 21st Century, 2024)
Socialization, as a problem of various pedagogical disciplines, is relevant at all times, since it contributes to the development of personal social skills, increases communicative competence and the formation of social identity. The relevance of the research is due to the fundamental changes taking place in various spheres of public life. In the 21st century, the development of society is characterized by integration processes in all spheres, including education. In conditions of universal inclusivity, the process of socialization of the child’s personality acquires a new meaning. In this context, the new approach involves considering the factors of the socialization process. The presented article is an integral part of the study of this problem, which presents various studies of biological factors of socialization and approaches to their significance. The purpose of this research is to study and compare different approaches to the importance of biological factors in the process of child socialization. The novelty of the study is that various points of view on the problem were studied and analyzed, and they were considered as a justification for the determining role of biological factors in the process of socialization of a child’s personality.